2021
DOI: 10.1093/brain/awab362
|View full text |Cite
|
Sign up to set email alerts
|

A brain atlas of axonal and synaptic delays based on modelling of cortico-cortical evoked potentials

Abstract: Epilepsy presurgical investigation may include focal intracortical single-pulse electrical stimulations with depth electrodes, which induce cortico-cortical evoked potentials (CCEP) at distant sites because of white matter connectivity. CCEPs provide a unique window on functional brain networks because they contain sufficient information to infer dynamical properties of large-scale brain connectivity, such as preferred directionality and propagation latencies. Here, we developed a biologically informed modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 61 publications
3
29
1
Order By: Relevance
“…This framework provides evidence that the IHTT estimates are the result of activity elicited by the visual stimulus. The estimated IHTT values are in the reported range of electrode-based and intracranial EEG studies (Saron and Davidson, 1989;Friedrich et al, 2017;Chaumillon et al, 2018;Lemarechal et al, 2022). The MRI data and EEG-based measures of the IHTT were used to estimate morphological properties of white matter axons.…”
Section: Discussionmentioning
confidence: 99%
“…This framework provides evidence that the IHTT estimates are the result of activity elicited by the visual stimulus. The estimated IHTT values are in the reported range of electrode-based and intracranial EEG studies (Saron and Davidson, 1989;Friedrich et al, 2017;Chaumillon et al, 2018;Lemarechal et al, 2022). The MRI data and EEG-based measures of the IHTT were used to estimate morphological properties of white matter axons.…”
Section: Discussionmentioning
confidence: 99%
“…First, SEEG signals were preprocessed to identify stimulation events, filter bad channels [72], and correct for stimulation artifacts [73]. Recordings with high likelihood of reflecting pathological activity were identified and discarded using Delphos software to mitigate the impact of epileptogenic processes in further analyses [39, 74]. CCEPs on each electrode contact were baseline corrected and z -scored based on the [−400, −10] ms time window before stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…Note that P and A are asymmetric, such that P ij may differ to P ji . Data from the F-TRACT project is openly available at https://f-tract.eu/ and further details on data acquisition and processing are provided in [37][38][39].…”
Section: F-tract Datasetmentioning
confidence: 99%
“…Some EEG studies have detected small changes during adolescence (7,8). After adolescence there may be little further maturation, as also indicated by one study of cortico-cortical evoked potentials (CCEPs), which reported a decrease in conduction delay of only one millisecond from before to after the age of 15 (9). Anatomical studies, however, indicate that the human connectome may follow a much longer developmental trajectory: postmortem studies have shown that myelination starts in the late prenatal period and continues into late adolescence (10).…”
Section: Introductionmentioning
confidence: 99%